Prevalence of incidental prostate cancer: A systematic review of autopsy studies. Issue 7 (21st April 2015) - Bell, Katy J.L.; Del Mar, Chris; Wright, Gordon; Dickinson, James; Glasziou, Paul
<x xml:space="preserve">Abstract</x> Prostate cancer screening may detect nonprogressive cancers, leading to overdiagnosis and overtreatment. The potential for overdiagnosis can be assessed from the reservoir of prostate cancer in autopsy studies that report incidental prostate cancer rates in men who died of other causes. We aimed to estimate the age‐specific incidental cancer prevalence from all published autopsy studies. We identified eligible studies by searches of Medline and Embase, forward and backward citation searches and contacting authors. We screened the titles and abstracts of all articles; checked the full‐text articles for eligibility and extracted clinical and pathology data using standardized forms. We extracted mean cancer prevalence, age‐specific cancer prevalence and validity measures and then pooled data from all studies using logistic regression models with random effects. The 29 studies included in the review dated from 1948 to 2013. Incidental cancer was detected in all populations, with no obvious time trends in prevalence. Prostate cancer prevalence increased with each decade of age, OR = 1.7 (1.6–1.8), and was higher in studies that used the Gleason score, OR = 2.0 (1.1–3.7). No other factors were significantly predictive. The estimated mean cancer prevalence increased in a nonlinear fashion from 5% (95% CI: 3–8%) at age <30 years to 59% (95% CI: 48–71%) by age >79 years. There was substantial variation between populations in estimated cancer prevalence. There is a substantial reservoir of incidental prostate cancer which increases with age. The high risk of overdiagnosis limits the usefulness of prostate cancer screening.